PENERAPAN ANALISIS SWOT MANAJEMEN PEMASARAN BISNIS DEVELOPER (Studi : Perumusan Strategi Pemasaran PT. Sinar Mulya Sejahtera Pekanbaru) - Hendri Yadi; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted on PT. Sinar Mulya Sejahtera, Pekanbaru city. The purpose of this study is to find the right marketing strategy to be applied in PT. Sinar Mulya Sejahtera with SWOT analysis.This research is a descriptive study with a qualitative approach. Where non population and sample. This study using key informan to obtain the information needed. The data used are primary data and secondary data. The primary data obtained from interview with the director PT. Sinar Mulya Sejahtera about the company profile and strategy of PT. Sinar Mulya Sejahtera.. Secondary data obtained from target sales and realized sales report.From the analysis conducted known that in recent years, product sales has decreased. The decrease can be happen because the company never knew and never do the analysis about market environment changes, market demand, and low marketing activities. SWOT analysis conducted to determine the strengths, weakness, opportuniteies, and threats in PT. Sinar Mulya Sejahtera. The marketing strategy formulated using SWOT Matrix. And strategic plan in short time and long time created after analysis with SWOT matrix.Keywords: Implementation, SWOT Analysis, Marketing Strategy, Strategic Plan